Development of a wireless sensor for vibration measurement - Chu, Joshua Yung Keung (Nanyang Technological University, 2020)
In the field of condition monitoring, wireless sensor networks have the advantage of standalone nodes monitoring assets in real-time and relaying readings to a database with minimal latency. This allows faults to be detected as soon as the results are analysed instead of during maintenance intervals. This project explores the use of wireless vibration sensors in the condition monitoring of train tracks in Singapore. Similar studies were reviewed to find suitable methods of data collection and analysis of vibration data. Several wireless sensors were assessed based on their performance characteristics for the suitability of the application. Experiments were also conducted in which vehicle-based wireless sensors were used to collect data on in-service trains to analyse the vibrations in attempt to identify vibration characteristics of the tracks. The results of the experiments showed that with the analysis methods in this report, it is possible to classify some vibrations due to the tracks using vehicle-based sensors.